A novel HLA‐B*15 allele, HLA‐B*15:326, was identified in a Chinese bone marrow donor. (22nd February 2016) - Chen, N.‐Y.; Zhang, W.; He, J.‐J.; He, J.; Zhu, F.‐M.
Abstract: HLA‐B*15:326 has one base substitution at position 176G>A in exon 2 compared with HLA‐B*15:01:01:01 .